Ministerial decree no 126/2014 on amending dome provision of the decree of the minister of finance no 554/2007 concerning the rules implementing the provisions of the social insurance law issued as per Law No. 79/1975 = قرار وزاري رقم 126 لسنة 2014 بتعديل بعض أحكام قرار وزير المالية رقم 554 لسنة 2007 بشأن القواعد المنفذة لأحكام قانون التأمين الاجتماعي الصادر بالقانون رقم 79 لسنة 1975 - Egypt; The middle east library for economic services, translator. (2025)
Ministry of social solidarity decree no. 126 of the year 2014 issued on 28/12/2014 on amending some provisions of the decree of the minister of finance no. 554 of the year 2007 concerning the rules implementing the provisions of the social insurance law issued as per law no. 79 of the year 1975 وزارة التضامن الاجتماعى قرار رقم 126 لسنة 2014 الصادر بتاريخ 28/12/2014 بتعديل بعض أحكام قرار وزير المالية رقم 554 لسنة 2007 بشاأن القواعد المنفذة لأحكام قانون التأمين الاجتماعى الصادر بالقانون رقم 79 لسنة 1975